Venture Capital Regulation Reform: Revitalization of Venture Capital as an Alternatives Financing Mentorship and Partnership Based - Abubakar, Lastuti; Handayani, Tri (Faculty of Law, Universitas Negeri Semarang, 2019)
The growth of Venture Capital Company (PMV) in Indonesia is progressive although not significant. The Characteristics of Venture Capital, which is temporary in equity participation, caused venture capital financing is being highly risky financing. To anticipate this risk, PMVseeks the Investee Company (PPU) as a partner who is obliged to return capital. This is to secure this investment by using the concept of financing by venture capital. In addition, a guarantee agreement can be executed if Investee Company did not carry out obligations. This research aims to examine and analyze the essence of venture capital as an alternative financing mentorship and partnership based. In addition, it examines the position of collateral in financing venture capital. This study uses a normative juridical approach with descriptive analytical research specifications and qualitative juridical analysis. The initial concept financing of venture capital as equity participation that using mentorship and partnership turns into loan based financing with collateral. The regulations reform of venture capital through OJK Regulation is aim to expand the objectives of Venture Capital as an effort to anticipate the development of technology based and start up business. In addition, regulation reform of on Venture Capital aims to strengthen venture Capital through the authority of PMV/PMVSto manage Venture Fund. Legal reform of Venture Capital must be interpreted and implemented in line with the purposes of venture Capital as an alternative financing that prioritizes mentorship and partnership between PMV/PMVSand PPU. Beside the supervision by the OJK, the Venture Capital Agreement is an instrument to empower Venture Capital for MSMEs financing optimally. Keywords: revitalization of venture capital; law reform of venture capital; financing mentorship based